Sexual Activity and Menopause: Understanding Sexual Dysfunction in Menopausal Women (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sexuality is a significant part in the lives of menopausal ladies. The expansion of phosphodiesterase type 5 inhibitors for the treatment of male erectile brokenness in mix with longer future has affected perspectives and desires to keep up sexual working. Regardless of the significance of sexual capacity in menopausal ladies,sexual brokenness increments with age. Age-related decrease in sexual capacity may essentially diminish personal satisfaction, making acknowledgment of sexual brokenness by doctors significant for getting menopausal ladies viable consideration. Sexual brokenness can result from numerous etiologies including psychosocial factors, medicine results, vulvovaginal decay, constant sickness, or hypoactive sexual longing problem (HSDD). Finding the etiology and recognizing modifiable elements of the sexual capacity will help characterize suitable treatment.